2022
DOI: 10.1126/sciadv.abb7348
|View full text |Cite
|
Sign up to set email alerts
|

The ripple effects of funding on researchers and output

Abstract: Using unique, new, matched UMETRICS data on people employed on research projects and Author-ity data on biomedical publications, this paper shows that National Institutes of Health funding stimulates research by supporting the teams that conduct it. While faculty—both principal investigators (PIs) and other faculty—and their productivity are heavily affected by funding, so are trainees and staff. The largest effects of funding on research output are ripple effects on publications that do not include PIs. While… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Its simplicity suggests that sustained increases in available scientific labor for any reason, to an individual research group or to an entire institution, can be expected to proportionally increase scientific productivity. This prediction is supported by recent work on the effects of grant funding on faculty, graduate, and postdoctoral hiring and productivity (37). Our results enrich that understanding by uncovering the role of prestige: Prestigious institutions receive far more funding, which equates to more available research labor, and, in disciplines with collaboration norms, that labor advantage drives greater faculty productivity via coauthorship (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…Its simplicity suggests that sustained increases in available scientific labor for any reason, to an individual research group or to an entire institution, can be expected to proportionally increase scientific productivity. This prediction is supported by recent work on the effects of grant funding on faculty, graduate, and postdoctoral hiring and productivity (37). Our results enrich that understanding by uncovering the role of prestige: Prestigious institutions receive far more funding, which equates to more available research labor, and, in disciplines with collaboration norms, that labor advantage drives greater faculty productivity via coauthorship (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…30 Less access to funding or less funding for women means that it is less likely the research will be completed as proposed and can lower the productivity levels of women. 31 Studies also show that from assistant professor through professor, the h-index increases with subsequent academic rank. 32 However, women are often under-represented in positions of high rank in ophthalmology societies and are not being promoted to positions of professorship or faculty at the same rate as men or women in other specialties.…”
Section: Discussionmentioning
confidence: 98%
“…A Hong Kong-based study showed that women received more funding from their institutions, but men were more likely to receive public research funding, showing that man academics access a more comprehensive range of external funding 30. Less access to funding or less funding for women means that it is less likely the research will be completed as proposed and can lower the productivity levels of women 31…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the United States allocates a significant number of resources to scientific research (National Science Board, National Science Foundation, 2022), offering considerable funding opportunities for both academic and industry-driven research. This not only encourages research activities but also supports research teams in conducting their studies (Sattari et al, 2022).…”
Section: Discussionmentioning
confidence: 99%